The work of a social educator with adolescents in the community - Қыяқбаева, Ұлбосын; Иниятова, Айдана; Асанханова, Жанна; Шырынбаева, Гүлбахира; Сураншиева, Мейрамгул (Pedagogy and Psychology, 2020)
The authors of the article emphasizes the work of a social pedagogue with adolescents at their place of residence and to protect adolescents or children who need social assistance, guided by their place of residence, marital status and educational environment in his / her social environment. social work and identification of the main problems of the child, creating a comfortable atmosphere for adolescents and children at their place of residence, marital status and educational environment in his / her social environment. social work and identification of the main problems of the child, creating a comfortable atmosphere for adolescents and children in their place of residence, the main issue of creating a favorable atmosphere for adolescents and children in the community, promoting social work in the context of renewed education, adaptation to society and a place where be found in the social environment, as well as adaptation to society and the place where they live in the social environment.